ANALISIS KUALITAS PELAYANAN, KEPERCAYAAN SERTA CITRA KOPERASI TERHADAP KEPUASAN DAN LOYALITAS ANGGOTA - Sutrisno Sutrisno; Dwi Cahyono; Nurul Qomariah (Jurnal Sains Manajemen dan Bisnis Indonesia, 2017)
ABSTRACTThe purpose of this study is to analyze the influence of service quality, trust, image of cooperative to the satisfaction and loyalty of members. Quantitative descriptive research type with explanatory research design. The population in this study is all members of Koprimka "Anjasmoro" Jember. The sample used was 84 respondents, using calculation with slovin formula. Analyzer uses path analysis. The result of hypothesis test shows that service quality, trust, image of cooperative individually have a significant positive effect on member satisfaction. Quality of service, trust and image of cooperatives individually positively significant effect on member loyalty through member satisfaction. Member satisfaction positively significant influence on member loyalty. The analysis of coefficient of determination on model 1 shows that 44.6% satisfaction of members of Koprimka "Anjasmoro" is influenced by service quality, trust and image of cooperative, while the rest 55.4% influenced by other variables outside model or equation. Determination coefficient analysis in model 2 shows that service quality, trust, cooperative image and member satisfaction can influence member loyalty by 60.4%, while the remaining 39.6% is influenced by other variables outside model or equation.Keywords: service, trust, image, satisfaction and member loyalty